Reflections by C. S. Lewis on Biblical Narrative as a Literary Phenomenon: The Cathartic Example of the Youth Literary Cycle The Chronicles of Narnia - Cintia Carreira Zafra (Multidisciplinary Journal of School Education, 2022)
This essay provides a detailed exploration of interest in the Bible as a literary phenomenon. We start with Frye’s research in order to analyze academic perspectives that studied the Bible as a form of literary criticism. Among these perspectives, it is worth highlighting those that define biblical narrative as the principal element of the Western imaginative tradition. This phenomenon builds a set of interrelations that have shaped our specific literary tradition, imbuing it with this symbiosis between sacred and profane influences. Moving on to a second level of interpretation of the question at hand, we examine the encounter between secular and religious literatures as a consequence of the work initiated by Frye. The philological background of the writer C. S. Lewis is key and unprecedented in shedding light on the frontiers between reality and fantasy in the field of literary studies, as exemplified in The Chronicles of Narnia. The Narnia books allow their readers to experience catharsis. This experience  is foundational for the acquisition and cultivation of some character strengths, as the ancient Greek tradition held and put into practice centuries ago.